Dinasti Politik Di Indonesia Dalam Perspektif Hukum Islam - Sahara Aulia Nasution; Effira fatin zahra Butar Butar; Dinda Zihan Milfah Darmanto; Putri amanda Putri; Ahmad Al Bukhori Bukhori (Tabayyun : Journal Of Islamic Studies, 2023)
Islam has no a complete and ready-made political system and governance, including the discussion about the political dynasty. The phenomenon of political dynasties has occurred in Islamic history, also in Indonesia, in reform era from the regional to national level. If seen in legal aspect, there is no any policy prohibiting the practice of political dynasty in Indonesia, but if this still continues, it can threaten the sustainability of the Indonesian government and damage the substance of democracy as a system used in governance. This study aims to explain how the practice of political dynasty in Indonesia during the reform era and to explain how contemporary Siyasah Figh perspective, which in this case uses Muhammad Abid Al-Jabiri's political reasoning thoughts on the practice of political dynasties in Indonesia. The research method used in this research was library research that is by collecting data and information through the study of various library materials as research sources. The analysis technique in this study used content analysis. The results of this study showed that the practice of political dynasty in Indonesia has emerged any issues from the political to economic aspect. The increasing political dynasty in Indonesia is also determined by a number of factors, some of which are the absence of policy prohibiting the practice of political dynasty. In the perspective of al-Jabiri about the political rationale, it consists of three dominant motives: aqidah (faith), kabilah (tribes) and ghanimah. Al-Jabiri historically confirmed the practice of political dynasties. In practice, political dynasty in Indonesia, aqidah is defined as a political ideology, tribes as nepotism, and ghanimah as economic interests, both economic benefits from political dynasties, or economic interests to continue to grow a political dynasty.